Edward Tulane’s Character Development in Kate Dicamillo’s the Miraculous Journey of Edward Tulane - Azaliasari Aqmarina (Universitas Gadjah Mada, 2014)
This article examines a novel entitled The Miraculous Journey of Edward Tulane by Kate Dicamillo. It aims to identify the character development of Edward Tulane, to determine the cause of his change and to find out its meaning of it applies objective approach. The result indicates that Edward Tulane’s character is developing from an arrogant to caring rabbit china doll.